2020
DOI: 10.3390/jcm9072106
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and COVID-19: A Systematic Scoping Review

Abstract: Older people have paid a huge toll in terms of mortality during the coronavirus disease-19 (COVID-19) pandemic. Frailty may have contributed to the vulnerability of older people to more severe clinical presentation. We aimed at reviewing available evidence about frailty and COVID-19. We searched PUBMED, Web of Science, and EMBASE from 1 December 2019 to 29 May 2020. Study selection and data extraction were performed by three independent reviewers. Qualitative synthesis was conducted and quantitative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 50 publications
(176 reference statements)
2
116
0
6
Order By: Relevance
“…22 The different strategies have been adopted in different countries with selective admission of younger patients, and donot-resuscitate labeling has highlighted the problem of "ageism". 12 Data from the United States and China showed that people aged older than 65 years represent half of the hospital admissions, more than half of the admissions to the ICU, and account for 80% of deaths related to COVID-19. 23 , 24 Thus, it is clear that older people are at an increased risk for adverse outcomes due to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 The different strategies have been adopted in different countries with selective admission of younger patients, and donot-resuscitate labeling has highlighted the problem of "ageism". 12 Data from the United States and China showed that people aged older than 65 years represent half of the hospital admissions, more than half of the admissions to the ICU, and account for 80% of deaths related to COVID-19. 23 , 24 Thus, it is clear that older people are at an increased risk for adverse outcomes due to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…4 , 5 Although frailty has shown to be a reliable predictor of clinical and healthcare-related outcomes in various conditions, 6 , 7 the outcomes of frail older patients diagnosed with COVID-19 remain unclear and arguable. [8][9][10][11][12][13] In the current study, we aimed to assess the prevalence of frailty, the predictive value of frailty for adverse outcomes if any, and lastly, the value of adding frailty to the contemporary comorbidity-based risk adjustment tools in our nationwide COVID-19 patients.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…This criterion seems to be associated with the idea of frailty [ 61 ] and chronic comorbidities [ 62 ], suggesting that increasing age leads to a higher probability of death [ 47 ]. Replacing the age criterion with the frailty assessment seems to better determine the risk of worse health outcomes and avoids age discrimination in the screening protocols [ 63 ]. On the other hand, carrying out assessments based on frailty to determine the probability of survival may constitute indirect discrimination as the elderly and people with specific disabilities may be considered more fragile [ 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some scientific societies are recommending assessing frailty in patients with COVID-19 infection to guide their triage and the results seem to be promising (17). Considering scientific literature, frailty was only investigated regarding its association with overall mortality, hospital contagion, intensive care unit admission rates, and disease phenotypes (18). According to a recent systematic scoping review, specific interventions in relation to frailty or its impact on COVID-19 treatments have not been evaluated yet (18).…”
Section: Frailtymentioning
confidence: 99%